Productive Employees in SMEs: Exploring the Influence of Work Discipline and Turnover Intention - Suparman, Dadang; Rahayu, Siti Widhiyanti (International Journal of Business, Law, and Education, 2026)
This study explores the influence of work discipline and turnover intention on employee productivity in SMEs. The research design adopts an explanatory survey model. The research instrument was distributed to collect responses from 57 respondents across 14 SMEs in the creative industry sector in the Indonesian context, using a probability sampling method with a non-proportional sampling technique. The data analysis method applies instrument validity and reliability tests, as well as collinearity tests estimated using a multiple linear regression model, and evaluates predictive power using the R2 criterion. The significance tests for individual and simultaneous influences are evaluated using the t- and F-statistics, with thresholds of>1,96 at an alpha of 0,05. The research findings confirm that work discipline and turnover intention have a positive and significant influence on employee productivity among SMEs in the creative industry sector, both individually and simultaneously. Work discipline and turnover intention together can explain variance in employee productivity, with moderate predictive ability. However, turnover intention has a more dominant influence on employee productivity in SMEs than work discipline. Evaluating employee turnover rates and work discipline is crucial in SMEs, and HR management must manage them appropriately, decisively, conservatively, and regularly to significantly impact employee productivity and strengthen sustainable business competitiveness at the organisational level.